2009
DOI: 10.3109/13697130903060081
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern of traditional Chinese medicine for climacteric women in Taiwan

Abstract: Women of climacteric age in Taiwan utilized TCM more often than other age groups. To deal with multiple symptoms and/or diseases among climacteric women, new prescription patterns of combining two or more herbal formulae have evolved. Studies on safety issues and drug-herb interactions are warranted for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 17 publications
(12 reference statements)
0
26
0
Order By: Relevance
“…This tendency might be amplified when considering TCM use [36]. Second, we suggested that women had more opportunities to use TCM for maintaining regular menstruation, [37] promoting health during pregnancy [38]-[41], and treating post-menopausal syndrome in climacteric age [42]. Third, women may use acupuncture treatment to reduce body weight, waist circumference and body mass index to improve their body image [34], [43].…”
Section: Discussionmentioning
confidence: 98%
“…This tendency might be amplified when considering TCM use [36]. Second, we suggested that women had more opportunities to use TCM for maintaining regular menstruation, [37] promoting health during pregnancy [38]-[41], and treating post-menopausal syndrome in climacteric age [42]. Third, women may use acupuncture treatment to reduce body weight, waist circumference and body mass index to improve their body image [34], [43].…”
Section: Discussionmentioning
confidence: 98%
“…Shu-Jing-Huo-Xie-Tang is able to relieve both arthralgia and muscle pain. In previous studies, Shu-Jing-Huo-Xie-Tang was the most commonly prescribed herbal formula for diseases of the musculoskeletal system and connective tissue in climacteric women [13] and the second most commonly used herbal formula in Taiwan during 2004 [14]. Although TCM physicians in Taiwan frequently prescribe Shu-Jing-Huo-Xie-Tang, its effectiveness and safety is uncertified based on clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Jia-Wei-Xiao-Yao-San, the fourth most commonly prescribed herbal formula for osteoporosis, was also the most commonly used CHP for the relief of menopausal symptoms [13]. According to previous studies, Jia-Wei-Xiao-Yao-San can be prescribed to relieve hot flushes and other menopausal symptoms, including insomnia and emotional disturbance [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the key independent variables for the utilization of CHP among CRC survivors, we selected the demographic factors according to previous studies 21, 22, 23, 24. Patients were classified, based on age, into one of six groups, as follows: ≤39, 40–49, 50–59, 60–69, 70–79, and ≥80 years.…”
Section: Methodsmentioning
confidence: 99%